Inheritance of protein markers in the succession of generations of interspecific hybrids of cotton - Sh. Yunuskhanov; Z. Abdurazakova (Вавиловский журнал генетики и селекции)
This paper presents the results of studying the inheritance of protein markers in different generations of interspecific hybrids of cotton Gossypium hirsutum L. × G. barbadense L. and G. barbadense L. × G. hirsutum L. While these hybrids were in development, the species G. hirsutum was represented by dwarf plants and the species G. barbadense, by variety C-6037 plants. G. hirsutum plants had protein marker H-0.13 and G. barbadense plants had the homologous marker, protein B-0.18. Previous studies demonstrated that in interspecific crosses these markers behave as alleles of the same locus. This allowed these markers to be used for analysis of the ratios of phenotypic classes in the succession of generations of interspecific hybrids, including F2, F9 and F10. In these studies, the plants with only one type of protein (H-0.13 or B-0.18) were regarded as homozygous for the corresponding gene, while plants with both proteins (H-0.13 and B-0.18), as heterozygous. Some polymorphic progeny showed a significant shift in the ratios of phenotypic classes. These changes were observed as an increased or a decreased share of a particular phenotypic class, or as a significant increase or decrease in the proportion of the heterozygotes. The electrophoretic protein composition of cotton seed samples remained unchanged until the tenth generation of hybrids, but in the tenth generation, some heterozygous plants gave offspring, the seeds of which lacked protein with an electrophoretic mobility of 0.70. Plants in which this protein was absent belonged to the homozygous phenotypic class with marker H-0.13.